Divergent responses of soil organic carbon fractions, aggregation and microbial communities to straw incorporation strategies along temporal and soil depth gradients in Mollisols - Mengmeng Qu; Bowen Zhang; Xinyi Huang; Huancheng Pang; Han Zhang; Song Guan; Sen Dou (Biology and Fertility of Soils, 2026)

Deep Learning-Enhanced Adaptive Correntropy Factor Graph Optimization for robust UUV navigation - Sen Cheng; Yanyan Wang; Bin Sun; Haitao Zhu; Xianqiang Qu (Ocean Engineering, 2026)

A robust INS/USBL/DVL integrated navigation method based on adaptive correlation entropy factor graph optimization - Sen Cheng; Yanyan Wang; Qinglong Zhao; Haitao Zhu; Xianqiang Qu (Ocean Engineering, 2026)

Temporal dynamics of insecticide-resistance mutations in the diamondback moth Plutella xylostella (Linnaeus, 1758) within northern immigration regions - Ya-Jun Qu; Jin-Cui Chen; Hui-Juan Li; Shuai-Yu Wang; Xue-Yan Zhang; Ary A. Hoffmann; Sen-Shan Wang; Shu-Jun Wei (Journal of Asia-Pacific Entomology, 2026)

Detoxifying zinc oxide nanoparticles during sludge anaerobic digestion in the presence of polyferric sulfate - Yongkui Yang; Junxiang Huang; Sen Qu; Guangxue Wu; Yiwen Liu; Yifeng Ling; Peizhe Sun; Yingxin Zhao; Lin Zhao (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “A high-sensitive PDMS-based sensor with a wide sensing range by fabricating refined and reconstructable conductive network” [Chem. Eng. J. 507 (2025) 160626] - Shuaishuai Zhou; Huanhuan Zhang; Qian Chen; Qing-wen Yuan; Sen-hao Zhang; Nannan Bao; Jin-Ping Qu (Chemical Engineering Journal, 2025)

A High-Sensitive PDMS-Based sensor with a Wide Sensing Range by fabricating refined and reconstructable conductive network - Shuaishuai Zhou; Huanhuan Zhang; Qian Chen; Qing-wen Yuan; Sen-hao Zhang; Nannan Bao; Jin-Ping Qu (Chemical Engineering Journal, 2025)

Interspecific predation of a native herbivore facilitates colonization by fall armyworms, Spodoptera frugiperda - Yingying Song; Kangwen Sun; Sen Guo; Zhaoke Dong; Ritao Qu; Hongying Cui; Wenxiu Guo; Baohua Ye; Lili Li; Yuyong Liang; Xingyuan Men (Journal of Pest Science, 2025)

The relationship between serum coagulation parameters and the recurrence of chronic subdural hematoma - Zhen Bao; Sen Xu; Gang Cui; Jian-Min Qu; Tian-Yu Liang (Molecular and Cellular Biochemistry, 2025)

Melatonin reduces postharvest decay of blueberries by regulating ascorbate–glutathione cycle and membrane lipid metabolism - Sen Cao; Linxiang Qiao; Tianyu Huang; Yu Zhang; Guangfan Qu; Xiaohong Kou (Postharvest Biology and Technology, 2024)

Free-standing, robust, hyperconnective hybrid nanofiber nonwovens enabled by interpenetrating network for oily aerosols purification - Weitao Zhou; Yiming Li; Zeng Qu; Sen Li; Ting Wu; Jingliang Li; Tingting Shi; Jikai Chen; Boyu Li; Haitao Huang; Shan Du (Chemical Engineering Journal, 2024)

Correction to: The relationship between serum coagulation parameters and the recurrence of chronic subdural hematoma - Zhen Bao; Sen Xu; Gang Cui; Jian-Min Qu; Tian-Yu Liang (Molecular and Cellular Biochemistry, 2024)

A new approach to extract the upright maize straw from Sentinel-2 satellite imagery using new straw indices - Jingping Zhou; Xiaohe Gu; Cuiling Liu; Wenbiao Wu; Yuchun Pan; Qian Sun; Sen Zhang; Xuzhou Qu (Computers and Electronics in Agriculture, 2024)

Dynamic behaviors of cavitation bubbles near biomimetic surfaces: A numerical study - Hongbo Shi; Hang Zhang; Linlin Geng; Sen Qu; Xikun Wang; Petr A. Nikrityuk (Ocean Engineering, 2024)

Hyperspectral estimation of maize (Zea mays L.) yield loss under lodging stress - Qian Sun; Xiaohe Gu; Liping Chen; Xuzhou Qu; Sen Zhang; Jingping Zhou; Yuchun Pan (Field Crops Research, 2023)

Carvacrol exhibits direct antifungal activity against stem-end rot disease and induces disease resistance to stem-end rot disease in kiwifruit - Tingting Mi; Donglan Luo; Jiangkuo Li; Guangfan Qu; Yanzheng Sun; Sen Cao (Physiological and Molecular Plant Pathology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Numerical simulation of free-surface waves past semi-submerged two-dimensional rectangular prisms with different aspect ratios and rounding chamfer radii - Sen Qu; Shengnan Liu; Muk Chen Ong; Xikun Wang; Shuzheng Sun (Ocean Engineering, 2023)

Fabrication of outstanding mechanical performance engineered poly (lactic acid)/thermoplastic poly(ester)urethane in-situ nanofiber composites with a large-scale industrial innovation methodology - Yue He; Cong Fang; Wen-Hua Xu; Ling-Cao Tan; Sen Qin; Xiao-Chun Yin; Yan-Hong Feng; Chul B. Park; Jin-Ping Qu (Chemical Engineering Journal, 2023)

Numerical Investigation of Vortex-Induced Vibration of a Circular Cylinder with Control Rods and Its Multi-Objective Optimization - Zhiyang Hu; Jiaqi Chen; Sen Qu; Xikun Wang (Journal of Marine Science and Engineering, 2022)
The flow past a 2D circular cylinder with control rods is numerically simulated in the present paper. The suppression effects of the control rods on the vortex-induced vibration (VIV) characteristics of the cylinder are investigated using the overlapping grid method and user defined function. By setting the cylinder’s vibration amplitude and drag force coefficient as the expected objective function, a multi-objective optimization is carried out to enhance the suppression performance at different reduced velocities, for which the rod-to-cylinder diameter ratio, gap ratio, incidence angle and reduced velocity are used as design variables. The regression expressions, which are obtained by Box–Behnken design (BBD), are employed in nondominated sorting genetic algorithm II (NSGA-II) to minimize the objectives. It is found that both the optimized vibration amplitude and drag force coefficient exhibit a monotonically decreasing linear trend with the reduced velocity, and as the reduced velocity decreases, the range of the optimized points gradually decreases. Subsequently, the optimized cases are verified by CFD simulations and compared with the original cases. For the samples at the reduced velocity of 4, 5, and 6, the vibration amplitude after optimization decreases by 15.1%, 24.8%, and 21.6%, respectively.

Human Adipose-Derived Stem Cells Delay Muscular Atrophy after Peripheral Nerve Injury in Rats - Siwei Qu; Ning Ma; Weixin Wang; Sen Chen; Qi Wu; Yangqun Li; Zhe Yang (Cell Biochemistry and Biophysics, 2022)

Development and characterization of 135 SNP markers in chiton Acanthochitona rubrolineatus - Jirui Zhang; Yunqi Song; Chenghong Wang; Shukui Zhang; Zilin Jiang; Yan Ni; Ying Qu; Donghui Sun; Zhikai Xing; Sen Wu; Jiangyong Qu; Xumin Wang; et al. (Conservation Genetics Resources, 2022)

Development and characterization of 177 SNP markers in the mud shrimp Upogebia major - Chenghong Wang; Yunqi Song; Jirui Zhang; Donghui Sun; Ying Qu; Yan Ni; Zilin Jiang; Shukui Zhang; Zhikai Xing; Sen Wu; Jiangyong Qu; Xumin Wang; et al. (Conservation Genetics Resources, 2022)

Chemical constituents from the fruits of Piper longum L. and their vascular relaxation effect on rat mesenteric arteries - Dan Li; Rui Wang; Xiaohan Cheng; Jianfeng Yang; Yihui Yang; Huichong Qu; Sen Li; Shan Lin; Donghua Wei; Yuhua Bai; Xiaodong Zheng (Natural Product Research, 2022)

Impact factors of the accumulation, migration and spread of antibiotic resistance in the environment - Zibo Lin; Tao Yuan; Lai Zhou; Sen Cheng; Xu Qu; Ping Lu; Qiyan Feng (Environmental Geochemistry and Health, 2021)

Nutrients Other than Selenium Are Important for Promoting Children’s Health in Kashin-Beck Disease Areas - Yujie Ning; Xi Wang; Xiong Guo; Pan Zhang; Pengfei Qu; Feng Zhang; Sen Wang; Yanxia Lei; Mikko Lammi (Biological Trace Element Research, 2018)

Global Drivers of Russian Timber Harvest - Sai Liang; Sen Guo; Joshua P. Newell; Shen Qu; Yu Feng; Anthony S.F. Chiu; Ming Xu (Journal of Industrial Ecology, 2016)
Summary Russian forest resources are important for global carbon cycling. In contrast to traditional analyses that focus on the harvest and direct use of Russian timber resources (a.k.a. production‐based accounting), this study investigates how the consumption of nations drives Russian timber harvest (a.k.a. consumption‐based accounting or the Russian timber footprint). China is the biggest direct importer and final consumer of Russian timber. The United States, Japan, and major European countries directly import relatively small amounts of Russian timber, but serve to drive large amounts of Russian timber harvest through their final consumption. Through structural path analysis, individual supply chain paths are delineated to show linkages between Russian timber harvest and the final consumption of nations. Findings of this study inform consumption‐side measures for Russian forest conservation, for example, taking shared responsibility and improving the production efficiency of key sectors in consuming nations.

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

HBx and HBs regulate RhoC expression by upregulating transcription factor Ets-1 - Dongdong Qin; Kai Li; Jialin Qu; Sen Wang; Chengcheng Zou; Yanrui Sheng; Ailong Huang; Hua Tang (Archives of Virology, 2013)

Hepatitis B virus regulation of Raf1 promoter activity through activation of transcription factor AP-2α - Jialin Qu; Jianbo Li; Ke Chen; Dongdong Qin; Kai Li; Yanrui Sheng; Chengcheng Zou; Sen Wang; Ailong Huang; Hua Tang (Archives of Virology, 2013)